2002
DOI: 10.1017/s095267570200427x
|View full text |Cite
|
Sign up to set email alerts
|

Upstep and embedded register levels

Abstract: This article is concerned with an interesting upstep phenomenon in the intonation of some speakers of Southern dialects of German. It experimentally establishes the main properties of this upstep phenomenon, and discusses the theoretical consequences. The upstep occurs on the nuclear pitch accent of a non-final intonation phrase. It targets the phonetic height of the utterance-initial peak, regardless of downstepped peaks that intervene between the initial peak and the upstepped peak. The findings are argued t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
66
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(74 citation statements)
references
References 54 publications
(122 reference statements)
7
66
0
1
Order By: Relevance
“…Previous researchers have observed that higher prosodic domains are signaled by higher initial rises [Cooper and Sorensen, 1981;Ladd, 1988Ladd, , 1990Selkirk, 2005;Selkirk et al, 2003;Truckenbrodt, 2002]. We have seen that IP-initial rises are larger than MaP-initial rises in Japanese ( § 4.5; fig.…”
Section: Initial Hs Initial Rises and Declinationsupporting
confidence: 50%
See 1 more Smart Citation
“…Previous researchers have observed that higher prosodic domains are signaled by higher initial rises [Cooper and Sorensen, 1981;Ladd, 1988Ladd, , 1990Selkirk, 2005;Selkirk et al, 2003;Truckenbrodt, 2002]. We have seen that IP-initial rises are larger than MaP-initial rises in Japanese ( § 4.5; fig.…”
Section: Initial Hs Initial Rises and Declinationsupporting
confidence: 50%
“…A number of previous works have shown that constituent initial rises -rises from L% to the following H -are cross-linguistically larger at IP edges than at MaP edges [Ladd, 1988[Ladd, , 1990Selkirk, 2005;Truckenbrodt, 2002]. If clause boundaries involve IP boundaries, then clause-initial rises should be larger than VP-initial rises, which coincide with MaP boundaries.…”
Section: Initial Rises In Ip-initial and Map-initial Positionsmentioning
confidence: 99%
“…The pitch height of both H and L turning points falls steadily throughout the utterance, as observed also by Norlin (1989) and Rifaat (1991). We analyze this pattern as downstep within local register domains which reflect prosodic constituency, following Truckenbrodt (2002Truckenbrodt ( , 2004Truckenbrodt ( , 2007. In most declarative utterances the peak of the final pitch accent is realized much lower than would normally be expected from the preceding sequence.…”
Section: X42 the Intonational Phonology Of Ea X421 Main Ea Sentementioning
confidence: 99%
“…Information structure is rather a strong constraint on the realisation of prosodic structure (Calhoun, 2004a). Contrary to the assumption of ToBI, this structure is metrical, highly structured and linguistically relevant both within and across prosodic phrases (Ladd, 1996;Truckenbrodt, 2002).…”
Section: Information Structure and Prosodic Structurementioning
confidence: 77%